Recent Progress with In Situ Characterization of Interfacial Structures under a Solid–Gas Atmosphere by HP-STM and AP-XPS - Zhang, Huan; Sun, Haoliang; Shen, Kongchao; Hu, Jinping; Hu, Jinbang; Jiang, Zheng; Song, Fei (Materials, 2019)
Surface science is an interdisciplinary field involving various subjects such as physics, chemistry, materials, biology and so on, and it plays an increasingly momentous role in both fundamental research and industrial applications. Despite the encouraging progress in characterizing surface/interface nanostructures with atomic and orbital precision under ultra-high-vacuum (UHV) conditions, investigating in situ reactions/processes occurring at the surface/interface under operando conditions becomes a crucial challenge in the field of surface catalysis and surface electrochemistry. Promoted by such pressing demands, high-pressure scanning tunneling microscopy (HP-STM) and ambient pressure X-ray photoelectron spectroscopy (AP-XPS), for example, have been designed to conduct measurements under operando conditions on the basis of conventional scanning tunneling microscopy (STM) and photoemission spectroscopy, which are proving to become powerful techniques to study various heterogeneous catalytic reactions on the surface. This report reviews the development of HP-STM and AP-XPS facilities and the application of HP-STM and AP-XPS on fine investigations of heterogeneous catalytic reactions via evolutions of both surface morphology and electronic structures, including dehydrogenation, CO oxidation on metal-based substrates, and so on. In the end, a perspective is also given regarding the combination of in situ X-ray photoelectron spectroscopy (XPS) and STM towards the identification of the structure–performance relationship.